Aspek Kebencanaan Pada Kawasan Wisata - Rosyidie, Arief (Journal of Regional and City Planning, 2004)
Tourism has an important role in regional development particularly in the improvement of quality of life and human life. Many tourism activities have been developed in hazard areas and consequently it has risks to the disaster. Disaster in tourism areas influences the performance of tourism particularly the number of tourist who visit the areas. The impact of disaster depends on disaster characteristics, vulnerability, and capacity of tourism areas. The impact will be experienced not only by tourist and tourism employees but also by other sectors and population in the area, as well as other related areas. Based on the important role of tourism in site/regional development and the impact which might be causedbu the disaster, management of disaster particularly disaster mitigation is important in the development of tourism areas.Keywords: dampak kebencanaan, kawasan wisata, mitigasi